2016
DOI: 10.5465/amj.2013.0972
|View full text |Cite
|
Sign up to set email alerts
|

Relational Changes During Role Transitions: The Interplay of Efficiency and Cohesion

Abstract: This study looks at what happens to the collection of relationships (network) of service professionals during a role transition (promotion to a management role). Our setting is three professional service firms where we examine changes in relations of recently promoted service professionals (auditors, consultants, and lawyers). We take a comprehensive look at the drivers of two forms of network changes -tie loss and tie gain. Looking backward we examine the characteristics of the contact, the relationship, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 130 publications
1
39
0
1
Order By: Relevance
“…As employees experience modifications to the composition, configuration, and/or content of their networks, they undergo a process of identity reconstruction in which they must cope with the loss of their old role-relationship identities (Conroy & O'Leary-Kelly, 2014;Ebaugh, 1988), negotiate how they will coherently incorporate their new relational identities into their existing self-concept (Ibarra, 1999;Ibarra & Barbulescu, 2010), and may ultimately develop a new identity in which they have reconciled the loss of their former role identities with the acquisition of new role identities (Ashforth, 2001;Pratt, Rockmann, & Kaufmann, 2006). This transition and adaptation process for individuals is characterized by periods of liminality (the condition of being betwixt and between; Conroy & O'Leary-Kelly, 2014) and discontinuity, which can significantly impact the effectiveness by which they demonstrate their competencies and enact their roles in relation to those with whom they are connected (Ashforth & Saks, 1995;Jonczyk, Lee, Galunic, & Bensaou, 2016). Indeed, modifications to individuals' social networks potentially impair "taken for granted roles and routines, causing those in the organization to question fundamental assumptions about how they should act" (Maitlis & Christianson, 2014: 77).…”
Section: The Impact Of Network Modifying Hr Practices On Relational Imentioning
confidence: 99%
See 2 more Smart Citations
“…As employees experience modifications to the composition, configuration, and/or content of their networks, they undergo a process of identity reconstruction in which they must cope with the loss of their old role-relationship identities (Conroy & O'Leary-Kelly, 2014;Ebaugh, 1988), negotiate how they will coherently incorporate their new relational identities into their existing self-concept (Ibarra, 1999;Ibarra & Barbulescu, 2010), and may ultimately develop a new identity in which they have reconciled the loss of their former role identities with the acquisition of new role identities (Ashforth, 2001;Pratt, Rockmann, & Kaufmann, 2006). This transition and adaptation process for individuals is characterized by periods of liminality (the condition of being betwixt and between; Conroy & O'Leary-Kelly, 2014) and discontinuity, which can significantly impact the effectiveness by which they demonstrate their competencies and enact their roles in relation to those with whom they are connected (Ashforth & Saks, 1995;Jonczyk, Lee, Galunic, & Bensaou, 2016). Indeed, modifications to individuals' social networks potentially impair "taken for granted roles and routines, causing those in the organization to question fundamental assumptions about how they should act" (Maitlis & Christianson, 2014: 77).…”
Section: The Impact Of Network Modifying Hr Practices On Relational Imentioning
confidence: 99%
“…Indeed, modifications to individuals' social networks potentially impair "taken for granted roles and routines, causing those in the organization to question fundamental assumptions about how they should act" (Maitlis & Christianson, 2014: 77). Therefore, individuals engage in an adaptation process where they attempt to bridge the gap between what was and what is (Louis, 1980;Petriglieri, 2011) through efforts that are jointly psychological, requiring identity formation or reorientation (Ashforth & Saks, 1995;Ibarra, 1999), and behavioral, involving changes in relationships (Jonczyk et al, 2016).…”
Section: The Impact Of Network Modifying Hr Practices On Relational Imentioning
confidence: 99%
See 1 more Smart Citation
“…For example, with respect to organisational change, structural holes are found to be more conducive than cohesion for change initiatives that diverge significantly from the institution's status quo but not for less radical change initiatives (Battilana & Casciaro, ). Other work has found both cohesion and structural holes to impact the network structure transitions that occur following role transitions and promotions in organisations (Jonczyk et al, ). Still other studies have found cultural factors to play a contingency role in the relative importance of cohesion versus structural holes towards social capital (Chai & Rhee, ; Xiao & Tsui, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Cohesion and structural holes also affect how individuals acquire external knowledge and transform it into innovations (Tortoriello, ). These characteristics have been discussed as enabling or hindering social capital (Chai & Rhee, ; Gargiulo & Benassi, ), organisational change (Battilana & Casciaro, ), the change of network relations following transitions in professional roles (Jonczyk, Lee, Galunic, & Bensaou, ), and others. Prior literature, therefore, provides good support for investigating cohesion and structural holes as network structural antecedents to adaptation to EMR‐enabled patient‐care work in this study.…”
Section: Theoretical Backgroundmentioning
confidence: 99%